Genomic surveillance of 4CMenB vaccine antigenic variants among disease-causing Neisseria meningitidis isolates, United Kingdom, 2010–2016 - Rodrigues, C; Lucidarme, J; Borrow, R; Smith, A; Cameron, J; Moxon, E; Maiden, M (Centers for Disease Control and Prevention, 2018)
In September 2015, 4CMenB meningococcal vaccine was introduced into the United Kingdom infant immunization program without phase 3 trial information. Understanding the effect of this program requires enhanced surveillance of invasive meningococcal disease (IMD) Neisseria meningitidis isolates and comparison with prevaccination isolates. Bexsero Antigen Sequence Types (BASTs) were used to analyze whole-genome sequences of 3,073 prevaccine IMD N. meningitidis isolates obtained during 2010−2016. Isolates exhibited 803 BASTs among 31 clonal complexes. Frequencies of antigen peptide variants were factor H binding protein 1, 13.4%; Neisserial heparin-binding antigen 2, 13.8%; Neisseria adhesin A 8, 0.8%; and Porin A-VR2:P1.4,10.9%. In 2015−16, serogroup B isolates showed the highest proportion (35.7%) of exact matches to >1 Bexsero components. Serogroup W isolates showed the highest proportion (93.9%) of putatively cross-reactive variants of Bexsero antigens. Results highlighted the likely role of cross-reactive antigens. BAST surveillance of meningococcal whole-genome sequence data is rapid, scalable, and portable and enables international comparisons of isolates.